ANALISIS KOMPARATIF KINERJA KEUANGAN BANK SYARIAH DI KAWASAN ASIA TENGGARA - Firdaus, Firdaus; Hambali, Risman; Ziani, Alvi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2023)
This research is motivated by the large gap in terms of assets, Islamic banks in Southeast Asia are still far behind when compared to the Middle East region. Meanwhile, the development of Islamic banking in Southeast Asia has not spread evenly and thoroughly. This study analyzes the comparison of the financial performance of Islamic banks in the Southeast Asian region in terms of the NPF, FDR, ROA, ROE and CAR ratios for the 2016-2020 period. The sample of this study consists of three Islamic banks in three countries (Indonesia, Malaysia and Brunei Darussalam) that publish their financial statements. The Kolmogorov-Smirnov/Shapiro-Wilk test was used to test the normality of the data. Meanwhile, ANOVA and Kruskal-Wallis tests were used for hypothesis testing. The results of this study show that there are significant differences in the financial performance of Islamic banks in Indonesia, Malaysia and Brunei Darussalam as measured by the NPF, FDR, ROA, ROE and CAR ratios for the 2016-2020 period.